Three new records of Lamiaceae from China and Uzbekistan - Zhao, Yue; Chi, Jian-Cai; Chen, Ya-Ping; Liang, Cun-Zhu; Turginov, Orzimat T.; Pulatov, Sardor O.; Rakhmatov, Abdurashid A.; Aromov, Tolmas B.; Xiang, Chun-Lei (Phytotaxa, 2022)
Geographic novelties of three species of Lamiaceae are newly reported in this paper. Phlomoides zenaidae, previously known only from a few collections from Kazakhstan, is reported from Xinjiang Province, China for the first time. Phlomoides baldschuanica and Nepeta badachschanica, previously only known from Tajikistan, are also newly reported for Uzbekistan. Diagnostic characters, additional descriptions, detailed illustrations, taxonomic comments and conservation status are provided.